Correction to: Development and validation of [18 F]-PSMA-1007 PET-based radiomics model to predict biochemical recurrence-free survival following radical prostatectomy. - Li, Tiancheng; Xu, Mimi; Yang, Shuye; Wang, Guolin; Liu, Yinuo; Liu, Kaifeng; Zhao, Kui; Su, Xinhui (European Journal of Nuclear Medicine & Molecular Imaging, 2024)
This document is a correction notice for an article titled "Development and validation of [18 F]-PSMA-1007 PET-based radiomics model to predict biochemical recurrence-free survival following radical prostatectomy" published in the European Journal of Nuclear Medicine & Molecular Imaging. The correction addresses an error in Figure 7 of the original article. The incorrect version of the figure is shown, followed by the correct version. The correction has been made by the authors. The publisher, Springer Nature, remains neutral in terms of jurisdictional claims and institutional affiliations. The authors of the article are Tiancheng Li, Mimi Xu, Shuye Yang, Guolin Wang, Yinuo Liu, Kaifeng Liu, Kui Zhao, and Xinhui Su.